SRAP as an Informative Molecular Marker to Study the Fusarium poae Genetic Variability - Dinolfo, María Inés (2015)
Fusarium poaeis one of theFusariumspecies isolated from grains associated with Fusarium head blight (FHB), whose occurrence has increased in the last years. In this study, a total of 105F.poaeisolates from Argentina, Belgium, Canada, England, Finland, France, Germany, Hungary, Italy, Luxembourg, Poland, Switzerland and Uruguay were evaluated using sequence-related amplified polymorphism (SRAP) to analyse the capacity of this molecular marker to evaluate theF.poaegenetic variability. The molecular analysis showed high intraspecific variability withinF.poaeisolates, and a partial relationship was revealed between variability and the host/geographic origin. Analysis of molecular variance (amova) indicated a high genetic variability in theF.poaecollection, with most of the genetic variability resulting from differences within, rather than between American and European populations. The analysis of sequenced SRAP fragments targets into hypothetical proteins from differentFusariumspecies showing that the SRAP technique not only allows studyingF.poaegenetic variability, but also targets coding regions into theF.poaegenome. To our knowledge, this is the first report on genetic variability ofF.poaeusing SRAP technique and also demonstrates the efficacy of this molecular marker to amplify open reading frames in fungus.